Textual Cohesion in “The Imam Fortify the Pillars of Religion with You” Poem by Ibn Marj Al-Kuhl Al-Andalusi - Al-Kafaween, Omar Faris (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aims to observe the linguistic and lexical mechanisms of textual cohesion in the poem, highlighting their role in representing meanings and rhythm, and their contribution to achieving this cohesion. Methods: The study employed a descriptive approach to observe and present the mechanisms of textual cohesion, using analysis to reveal the impact of these mechanisms in achieving textual cohesion and expressing meanings. Results: Mechanisms such as reference, conjunction, ellipsis, repetition, and collocation appeared more frequently in the poem, contributing to its textual and rhythmic cohesion. These mechanisms helped achieve textuality and express meanings leading to the main purpose, which is praise. Conclusions: The study identified and analyzed the prominent mechanisms of textual cohesion in the poem, showing their role in creating coherence among its parts and their impact on representing meanings and rhythm. It concluded that these mechanisms contributed to making the text cohesive and effective in conveying the purpose of praise to the audience. The researcher recommends paying attention to classical creative texts, especially those of Andalusian poets, and studying them according to modern critical theories.